Threatening others: Nicaraguans and the formation of national identities in Costa Rica - Sandoval García, Carlos (2004)
This short book by New Orleans anthropologist David Beriss is part of the Westview “Case Studies in Anthropology” series. This is a contemporary version of the long-established and similarly named “Case Studies in Cultural Anthropology,” originally published by Holt, Reinhart, and Winston. The latter series was a staple of the undergraduate curriculum and provided many of the ethnographies that students actually read. Like so much of the anthropology of its period, the series tended to have a “tribal” and rural focus: Many of the books were accounts of the Navaho, or the Banyoro, and so on, though other contributions went beyond that conventional remit. The Westview series is also concerned with “particular communities,” as its author guidelines put it, but as in much modern anthropology, the studies are not confined to a particular rural or urban locality. Indeed, Beriss’s excellent book is a wide-ranging account of transnational migrants from the Caribbean islands of Martinique and Guadeloupe who, over the last forty years in increasing numbers (perhaps a third of the island population), have gone to live and work in France.